Contraceptive Use, Access to Methods, and Program Efforts in Urban Areas - Ross, John A. (Frontiers in Global Women's Health, 2021)
This article uses two large sets of internationally comparable national surveys to analyze urban patterns of contraceptive use, access to methods, and fertility. Urban areas show higher use of contraception and lower fertility rates than rural areas, with substantial differences in the method mix. Urban women tend more toward the long-term methods of the intrauterine device (IUD), implant, and sterilization and less toward short-term, resupply methods. The overall use increases with education and with higher wealth quintiles. By regions, contraceptive use is unbalanced between urban and rural sectors especially in sub-Saharan Africa, where the overall levels of use are lowest. Overall, the urban fertility rate is only 70% of the rural rate. Across countries, the fertility rate correlates negatively with contraceptive use. National family planning programs tend to raise contraceptive use and to improve access to the methods. About half of the unmarried, sexually active women use contraception, with great diversity in which method is preferred. This holds for all married women as well: regions and countries show quite different patterns of use. Therefore, planners and donors should focus on the circumstances in individual countries.